Leveraging Customer Audit: A Decision Support Dashboard - Morgado, D.; Laureano, Raul M. S.; Diniz, M. (CISTI'2024 - 19th Iberian Conference on Information Systems and Technologies, 2024)
In the contemporary digital landscape, businesses harness formidable technological prowess to engage directly with customers and amass vast troves of consumer data. However, amidst this wealth of information, a critical gap persists in translating data into actionable insights that fuel business success. Traditional metrics fall short in capturing the intricate nuances of customer behavior and preferences, necessitating a shift towards more customer-base audit report systems. Drawing upon essential inquiries delineated in existing literature, this research aims to address pivotal questions integral to constructing an effective customer-base audit report. These inquiries encompass identifying customer segments, discerning differential value among customers, assessing revenue concentration, and forecasting customer retention. Through an exploration of data-driven methodologies and the development of a decision support dashboard, this research endeavors to furnish pragmatic guidance for organizations seeking to fortify their customer-centric reporting capabilities.